Xanthine dehydrogenase: An old enzyme with new knowledge and prospects. Issue 6 (1st November 2016) - Wang, Cheng-Hua; Zhang, Chong; Xing, Xin-Hui
ABSTRACT: Xanthine dehydrogenase (EC 1.17.1.4, XDH) is a typical and complex molybdenum-containing flavoprotein which has been extensively studied for over 110 years. This enzyme catalyzes the oxidation of purines, pterin and aldehydes with NAD + or NADP + as electron acceptor, and sometimes can be transformed to xanthine oxidase (EC 1.17.3.2, XOD) capable of utilizing oxygen as the electron acceptor. XDHs are widely distributed in all eukarya, bacteria and archaea domains, and are proposed to play significant roles in various cellular processes, including purine catabolism and production of reactive oxygen species (ROS) and nitric oxide (NO) in both physiological and pathological contexts. The recent applications of XDHs include clinical detections of xanthine and hypoxanthine content in body fluidics, and other diagnostic biomarkers like inorganic phosphorus, 5′-nucleotidase and adenosine deaminase. XDHs can also find applications in environmental degradation of pollutants like aldehydes and industrial application in nucleoside drugs like ribavirin. In this commentary, we would outline the latest knowledge on occurrence, structure, biosynthesis, and recent advances of production and applications of XDH, and highlighted the need to develop XDHs with improved performances by gene prospecting and protein engineering, and protocols for efficient production of active XDHs in response to the increasing demands.